Text messaging encryption system - Sundara Morthty, Nirmala Devi (2012)
Text Messaging Encryption system is a text message encryption and decryption.Encryption is a process of masking a message so that it is unreadable.Encryption is important to avoid other people to read certain information. The only way to read the information is to know the method on how message is being masked,in this case knowing the algorithm used to encrypt the message. Nowadays,most encryption and decryption processes are done by the computer.The main objective of this project is to build a text encryption and decryption system that will run on a Java enabled mobile phones.Then,the mobile phones will be used as an external means to encrypt text messages.As mentioned earlier,not only computers can encrypt and decrypt text but mobile phones also can encrypt and decrypt text messages.The purpose of this research is to provide security for confidential information to be sent over mobile phones.At the moment there is no security for messages transmitted over mobile phones.Confidential information or instructions can only be safely passed on to the required parties by email or verbally in person.This delays time and efficiency of crucial business operations. Currently messages in phone can easily be read if the phone is stolen,or users might simply send it to the wrong number.Messages need to be encrypted to solve this problem. With this only the sender and recipient will be able to send and receive private information. At present, banking,commerce and passwords can only be communicated with internet connection or as in person verbally or in written;Text Messaging Encryption system needs to overcome this intermediate subjects and deliver instructions or messages instantaneously and securely. The programming language that is used to write the program is Java Language.